Estudantes indígenas Tenetehara / Guajajara na Universidade Federal do Maranhão: análise sobre o acesso e permanência. - AMARAL, Verissa Einstein Soares do (2021)
This work continues with the research initiated in the conclusion of the Social Sciences course, whose theme was the analysis of affirmative action policies. The objective of this master's dissertation was to carry out a survey of theoretical categories to analyze the quota systems, investigating the access, entry and permanence of Tenetehara / Guajajara indigenous students at the Federal University of Maranhão - UFMA. It is a multidisciplinary theme, involving indigenous ethnology, education, law and politics. The methodology is inductive, being a qualitative research based on techniques such as participant observation, bibliographic analysis, semi-structured interviews, which make it possible to know and identify elements that directly influence the access and permanence of Tenetehara / Guajajara students at Universidade Federal do Maranhão. The main sources of analysis were legal documents related to access to higher education in Brazil and UFMA and documents related to the performance of the Indigenous Self-Declaration Verification Commission. Finally, it was possible to identify the principles that guide the formulation of compensatory policies for indigenous people and to characterize the strategies of construction and implementation of these policies at UFMA, demonstrating the effectiveness of the performance of the Verification Commissions and a little of the daily coexistence of indigenous students in the UFMA.